Comparison of Reading Speed Using Malay Unrelated Word Reading Chart with Standardized English Reading Charts - Buari, Noor Halilah; Azizan, Mardiah Farhana; Chen, Ai-Hong (International Journal of Medical and Health Sciences Research, 2014)
The objective of this study was to compare the reading speed of Malay language unrelated words reading chart named the Universiti Teknologi MARA unrelated words (UiTM-Muw) reading chart with Colenbrander reading chart and MNRead acuity chart. The participants were asked to read three different reading charts at random order, aloud and as quickly as possible. The time taken to read each chart was recorded and any error made while reading was noted. Reading speed was quantified as correct words read in a minute (cwpm). Comparison of reading speed showed a significant difference in reading speed between UiTM-Muw reading chart and Colenbrander reading chart [t(98)=-16.79, p=0.001] as well as MNread acuity chart [t(98)=-18.72, p=0.001]. However, weak agreement was found between reading speed of UiTM-Muw reading chart with MNRead acuity chart (mean difference = -83.6 cwpm) and Colenbrander reading chart (mean difference = -81.9 cwpm). Hence, UiTM-Muw reading chart in Malay language was incomparable with standardized English reading chart.